Nanozyme-enabled sensing strategies for determining the total antioxidant capacity of food samples. (1st August 2022) - Zhang, Fuyuan; Li, Yamei; Li, Xiaomeng; Liu, Ruobing; Sang, Yaxin; Wang, Xianghong; Wang, Shuo
Highlights: A new Au@Cu-HCF nanozyme was developed and characterized. A novel Au@Cu-HCF-based colorimetric strategy was developed for TAC in foods. A smartphone-based sensor was constructed based on the colorimetric strategy. Abstract: Gold doped copper hexacyanoferrate (Au@Cu-HCF) nanozyme-based colorimetric sensing strategies were exploited to measure total antioxidant capacity (TAC) of some plant-derived food samples. The new developed Au@Cu-HCF nanozyme replaces natural enzymes to catalyze a redox reaction, and antioxidants can compete with substrates in the interaction with OH, leading to an antioxidant concentration-dependent color change. Depending on the Au@Cu-HCF-based ABTS colorimetric strategy, a smartphone-based sensor was devised using smartphone's camera as a "smart detector". The proposed sensor was successfully utilized to measure the TAC of lotus root (4.61 mM), citrus juice (6.35 mM), and lemon beverage (1.00 mM) with standard deviations of 0.16 mM, 0.16 mM, and 0.06 mM, respectively. These results all agree well with the commercial kit (4.55 mM for lotus root, 6.27 mM for citrus juice and 1.11 mM for lemon beverage), indicating this sensor has good practical applications in the TAC measurement of food samples.